Identification of distinctive properties of common Malaysian honeys. (2021) - Yap, S.K.; Chin, N.L.
Abstract: The lack of information on quality of local Malaysian honey has caused it to be undervalued. To raise the awareness amongst consumers and increase its recognition, distinctive properties of Malaysian raw Kelulut, Tualang, and Akasia honey, including its physicochemical properties, antioxidant potential, and bacterial profile were studied and identified. Kelulut honey has a significantly (P < 0.05) higher water activity (0.787), lower pH (3.04) and higher acidity (347.5 meq/kg). The high acidity of Kelulut honey contributes to its unique sourly flavour and good antimicrobial properties. Tualang honey recorded significantly (P < 0.05) higher value of hydroxylmethylfurfural (51.5 mg/kg honey), DPPH radical scavenging activity (69.3%), and total phenolic content (1284.5 mgGAE/kg) which suggested its excellent antioxidant potential. The bacterial profiling of all three honey types revealed a significant presence of lactic acid bacterial genera in the Akasia (33.92%) and Kelulut (19.53%) honey, hence suggesting its good probiotic potential. Collectively, each type of honey possesses its unique distinctive feature attributed to its significantly different properties.